ANALISIS PENERAPAN TOTAL QUALITY SERVICE (TQS) TERHADAP CUSTOMER SATISFACTION PADA HOTEL PESONNA CABANG PEKANBARU - Ayu Setyaning Ajeng; Marpaung Jonnes M Rio; Paramita Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The acquisition of the Pesonna hotel consumer satisfaction index shows that the index in Pekanbaru City is the lowest compared to other cities in Indonesia. In operational studies, the application of total quality service needs to be supported by the capabilities and services of employees in achieving the success of the hospitality service industry sector to satisfy consumers. This study aims to analyze the effect of implementing total quality service on customer satisfaction at Hotel Pesonna Pekanbaru Branch. The population in this study were all consumers who visited the Pesonna Hotel Pekanbaru Branch. The sample in this study was taken using a purposive sampling technique with a total of 100 people. The primary data in this study were obtained from distributing questionnaires. Data analysis used simple linear regression. The results showed that the majority of consumer assessments of the total quality service provided by Hotel Pesonna belonged to the high category. Most customer satisfaction belongs to the satisfied category. In addition, based on regression analysis, it was found that there was a strong and significant positive effect of the application of total quality service (TQS) on customer satisfaction at Pesonna Hotel Pekanbaru Branch.Keywords: Total Quality Service, Customer Satisfaction, Pesonna Hotel